(untitled) (International Journal of Environmental Sciences, 2025)
Purpose :The microfinance Gross Loan Portfolio (GLP) stood at Rs. 381.2K crores in March 2025, declining 13.9% Y-O-Y and 2.6% Q-O-Q as lenders recalibrated strategies to manage stress. In Karnataka -7.0% Q-O-Q recorded GLP declines portfolio loans between Rs. 30K-50K. Microfinance has gained significant attention as a social innovation, providing flexible and low cost financial services to members who were not contacted by traditional services (JUja, S. V. 2014). The pre-eminent objective of the present paper on microfinance is to know to what extent the socio economic characteristics of respondents impacts on the study. Further, the study conducted to know before after joining of SHGs effect in case of occupation status and savings investment. Furthermore, the study also probe the factors driving women empowerment. Microfinance services are assisting both the unbanked and under banked and reduce poverty (John Agyekum Addae, 2018). Methodology :A previously known questionnaire was administered as schedule in order to urban research related data. Chi-square, contingency co-efficient modified ANOVA, Kendall’s co-efficient of concordance and weighted Arithmetic mean statistical tools were performed. Particulars are related to 6 taluks of Chikkaballapura district of Karnataka. Findings : The study found that all the demographic profiles of respondents sufficiently supporting the data. Study found a significant increase in certain occupation after joining SHGs. They include garlands making, petty business, vegetable selling and pickle / papad selling. The number of persons doing agriculture reduced from 18 to 8 after joining. As far as savings investments is concerned there exist substantial increase from 0 to 59 savings invested in SHGs, and very surprisingly there is a drastic decrease from 24 to 5 investors in chit funds after joining SHGs. Savings investment with relatives friends and neighbours also drastically reduced and it is a direct awareness realised from benefit of SHGs. The drivers out of 27 for which data collected three are ranked in the order. The first rank was awarded to savings formation, the second rank was awarded to savings formation, the second rank as per the study is employment and widespread social status and the third rank was awarded to women freedom movement.